The legitimacy of international law: challenges and prospects - Karvatska, S. B.; Chepel, O. D. (Аналітично-порівняльне правознавство, 2025)
The article is devoted to the study of the legitimacy of contemporary international law in the context of dynamic changes and unprecedented challenges. It is analyzed that traditional international law traditionally focuses its activities on states, which are its main subjects. However, in recent years, non-state actors such as transnational corporations and non-governmental organizations have gradually gained more influence. Since states are the main actors in the international system, international law is seen as a product of collective decision-making, where states voluntarily agree to abide by certain rules and obligations. In addition to challenges to the legitimacy of international law, new problems are emerging, such as cybersecurity, climate change, and the evolving nature of international law, which are seen as factors that create difficulties for the legitimacy of international law. It has been analyzed that systematic cooperation between international and national judicial bodies can harmonize the interpretation of international law. It has been proven that the legitimacy of international law is no longer a fixed category, as contemporary global challenges (information wars, climate change, the impact of technology) are constantly changing the nature of international interaction. Therefore, there is a need for a dynamic review of the criteria for legitimacy. The increasing role of non-traditional actors – non-governmental organizations, supranational institutions, digital platforms – broadens the understanding of who legitimizes international law and how. It is emphasized that although the inconsistency of the current international legal order in resolving emerging global crises is beyond doubt, a complete rejection of international law is not a solution to the problem. A strategic renewal of this system is needed through reforms that prevent states from using international law for self-serving purposes and create effective mechanisms to ensure compliance. Only through such a reset can international law restore its normative authority and function as a reliable foundation for global governance in the 21st century.